The expression of insulin signaling and N-methyl-D-aspartate receptor genes in areas of gray matter atrophy is associated with cognitive function in type 2 diabetes - Kesler, Shelli R; Cuevas, Heather; Lewis, Kimberly A; Franco-Rocha, Oscar Y; Flowers, Elena (Journal of Alzheimer's disease, 2025)
BackgroundType 2 diabetes (T2DM) is associated with brain abnormalities and cognitive dysfunction, including increased risk for Alzheimer's disease. However, the mechanisms of T2DM-related dementia remain poorly understood.ObjectiveWe evaluated the molecular properties of gray matter atrophy and cognitive decline in T2DM.MethodsWe obtained retrospective data from the Mayo Clinic Study of Aging for 271 individuals with T2DM and 542 non-diabetic controls (age 51-89, 62% male). We identified regions of significant gray matter atrophy in the T2DM group and then determined which genes were significantly expressed in these brain regions using imaging transcriptomics. We selected 15 candidate genes involved in insulin signaling, lipid metabolism, amyloid processing, N-methyl-D-aspartate-mediated neurotransmission, and calcium signaling.ResultsThe T2DM group demonstrated gray matter atrophy in regions of the default mode, frontal-parietal, and sensorimotor networks (p < 0.05 cluster threshold corrected for false discovery rate, FDR). , and genes were significantly expressed in these same regions (R > 0.10, p < 0.03, FDR corrected). Bayesian network analysis indicated significant directional paths among all 5 genes as well as the Clinical Dementia Rating score. Directional paths among genes were significantly altered in the T2DM group (Structural Hamming Distance = 12, p = 0.004), with expression becoming more important in the context of T2DM-related pathophysiology.ConclusionsAlterations of brain transcriptome patterns occurred in the absence of significant cognitive deficit or cortical amyloid accumulation and in the context of lower incidence of genotype, potentially representing an early biomarker of T2DM-related dementia.